Kemampuan Baca Tulis Al-Quran dan Korelasinya terhadap Kemampuan Matematika Mahasiswa Prodi Tadris Matematika IAIN Palopo - Hasri Hasri; Nur Rahmah (Al-Khwarizmi : Jurnal Pendidikan Matematika dan Ilmu Pengetahuan Alam, 2016)
This research is quantitative correlations designed ex-post facto. The population is all students of mathematics department from 2012/2013 until 2014/2015 IAIN Palopo totaling 291 people. The sampling technique used was proportional random sampling with a sample of 73 students. The collection data using by documentation and test. The result showed that: (1). The overview of the literacy al - Quran is 53 students from 73 have a very high ability (72,5%). This means that the literacy Quran students in terms of known/recognize letters hijaiyah, able to read the Quran and write some verses in the Quran have been classified as very good. (2). The mathematical ability is 50 students from 73 have a very high ability (68,5%). Thin means that that the ability of students in terms of reasoning, inductive reasoning, comprehension, problem solving, connections, communication, analytical thinking and creative thinking as well as a very good analogy are included, and (3). The ability to read and write Quran student has a significant correlation with math skills. This is based on the results of hypothesis testing inferential analysis that showed a correlation coefficient r = 0608 and the coefficient of determination r2 = 0.3697 or 36.97%. Interpretation of results is quite or moderate